IMPACT OF THE ACTIVITIES OF INTERNATIONAL FINANCIAL ORGANIZATIONS ON THE DEVELOPMENT OF NATIONAL LEGAL SYSTEMS - Kuzmin, Andrii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to analyze the role of the influence of international financial organizations on the legal systems of different countries, state policy in various spheres of public life. Studies of the normative and legal framework of countries, which regulates mutual relations in cooperation with international financial organizations. Research methods: a wide range of philosophical and worldview, general scientific and special scientific methods and approaches, which contributed to the solution of the main tasks of the research, especially the further identification from the standpoint of the specifics of the legal regulation of the activities of International Financial Organizations in various countries and the highlighting of the forms of their activity in the evolutionary development of international currency relations. The application of the descriptive method made it possible to characterize international financial organizations. The cooperation of countries with international financial organizations was analyzed using the formal legal method. The analysis method was used to study the current state of cooperation between countries and international financial organizations. Results: it was concluded that the cooperation of various countries with international financial organizations directly affects the implementation of one of the main principles of international law - independence. By attracting foreign capital to the budget, countries become completely dependent on the will of creditors, who in turn act exclusively in their own interests. Although certain progress can be observed in some areas of the country’s economic life, there is a need for strict legal regulation of the activities of international financial organizations in the country. Discussion: search and development of ways to overcome existing problems in the cooperation of countries with international financial organizations, as well as the study of norms regulating such relations, for the sake of their successful implementation in the national legislation of Ukraine.